A randomized controlled trial to compare clinical and cost-effectiveness of suture fixation versus tension band wiring for simple olecranon fracture fixation in adults: The Simple Olecranon Fracture Fixation Trial (SOFFT) protocol. (16th January 2023) - Cook, Elizabeth; James, Sophie; Watts, Adam C.; ,
Abstract : Aims: Olecranon fractures are usually caused by falling directly on to the olecranon or following a fall on to an outstretched arm. Displaced fractures of the olecranon with a stable ulnohumeral joint are commonly managed by open reduction and internal fixation. The current predominant method of management of simple displaced fractures with ulnohumeral stability (Mayo grade IIA) in the UK and internationally is a low-cost technique using tension band wiring. Suture or suture anchor techniques have been described with the aim of reducing the hardware related complications and reoperation. An all-suture technique has been developed to fix the fracture using strong synthetic sutures alone. The aim of this trial is to investigate the clinical and cost-effectiveness of tension suture repair versus traditional tension band wiring for the surgical fixation of Mayo grade IIA fractures of the olecranon. Methods: SOFFT is a multicentre, pragmatic, two-arm parallel-group, non-inferiority, randomized controlled trial. Participants will be assigned 1:1 to receive either tension suture fixation or tension band wiring. 280 adult participants will be recruited. The primary outcome will be the Disabilities of the Arm, Shoulder and Hand (DASH) score at four months post-randomization. Secondary outcome measures include DASH (at 12, 18, and 24 months), pain, Net Promotor Score (patient satisfaction), EuroQol five-dimension five-level score (EQ-5D-5L), radiological union, complications, elbow range of motion, and re-operations related to the injury or to remove metalwork. An economic evaluation will assess the cost-effectiveness of treatments. Discussion: There is currently no high-quality evidence comparing the clinical and cost effectiveness of the tension suture repair to the traditional tension band wiring currently offered for the internal fixation of displaced fractures of the olecranon. The Simple Olecranon Fracture Fixation Trial (SOFFT) is a randomized controlled trial with sufficient power and design rigour to provide this evidence for the subtype of Mayo grade IIA fractures. Cite this article: Bone Jt Open  2023;4(1):27–37.